An Empirical Study on Commuters Satisfaction Towards Chennai Metro Rail Limited - Kumar.S, shankar; B. Jeyaprabha, Dr. (International Journal of Engineering and Technology, 2018)
Commuter’s are the asset to any transport industry which is to be maintained carefully. All the employee including management must be involved in providing quality services to the commuter’s which leads to commuter satisfaction and retention. Commuter’s is one of the stakeholder of the business. In a competitive scenario commuter’s satisfaction becomes a top priority. The organization should achieve twin objective of customer satisfaction and commuter delight. So it is very much essential for every organization to find the factors which influence commuter’s satisfaction and should continuously monitor and nurture them. The research data is collected through structured questionnaire with a sample size of 60 respondents. It helps to find out the factors related to Chennai Metro Rail Limited services which have a impact on commuter’s satisfactions.